Proximate and ultimate analysis correction for kaolinite-rich Chinese coals using mineral liberation analysis. (15th December 2016) - Gräbner, Martin; Lester, Edward
Abstract: Since the ultimate analysis of the organic fraction of coal is a critical design figure for fixed-bed gasification processes, the analyses must be corrected to take into account the effect of the volatile mineral matter which can bias the analyses. In particular, the determination of water of constitution originating from clay minerals such as kaolinite remains an elaborate task. The present paper describes the application of Mineral Liberation Analysis (MLA) to estimate the content of water bearing kaolinite in a set of five samples originating from three Chinese coals (CC1 to CC3). In order to validate the MLA, one coal sample was investigated before and after density separation to assess the change in mineral matter. Results were compared to mineral content estimations from X-ray fluorescence (XRF) oxide ash analysis. In general, the MLA data can help to identify minerals better than XRF. MLA also has the advantage over XRD by detecting amorphous material, i.e. clay mineral types. The results indicate that kaolinite is the dominant clay mineral in each sample. The bias on the ultimate oxygen content (determined by difference) ranges between 1.7 and 8.9 wt% when comparing water-and-ash-free to dry-mineral-matter-free (dmmf) basis for CC2 and CC3 samples. In the case of CC1 coal, the change in the oxygen content is less than 1.2 wt% which is within experimental error for the accuracy of oxygen determination. Assuming that the organic coal fraction of the washed and unwashed CC2 samples are similar, it was concluded that the differences in dmmf ultimate analyses are greater for the MLA correction than for the XRF correction. Hence, MLA helps defining the type of mineral species present. Subsequently, SiO2 and Al2 O3 contents from XRF could be assigned to kaolinite and the water of constitution was estimated more precisely.